Mother Tongue Instruction and Foundational Mathematics Achievement: A Case Study of Primary Schools in Bara - Dahal, Prem Prasad; Shrestha, Kumar Narayan; Panta, Rudra Kumar (ILAM इलम, 2026)
In Nepal, Mother Tongue-Based Multilingual Education (MTB-MLE) is recognized as a crucial strategy for promoting inclusive and equitable early learning. As national policies encourage using students’ first languages in early grades, their practical effects on learning basic subjects like mathematics remain underexplored, especially in linguistically diverse areas like the Bara District. This qualitative study examines how the mother tongue—primarily Bhojpuri—affects teaching and learning of foundational mathematics in two public primary schools in Bara. Data were gathered through semi-structured interviews with six students, three primary teachers, classroom observations, and two headmasters. Although Nepali is the official medium of instruction, Bhojpuri predominantly shapes students’ linguistic environment. Thematic analysis showed that teaching in the mother tongue improved conceptual understanding, classroom engagement, and student participation. Similarly, it increased confidence among students when solving problems or asking questions, and better peer collaboration, especially when culturally relevant examples were used. These results suggest that mother tongue instruction fosters a supportive cognitive and emotional environment for learning mathematics. The study highlights the need for context-specific policies, locally developed teaching resources, and targeted teacher training to effectively implement MTB-MLE.